(untitled) (Pubmet, 2025)
The goal of the Innovation Lab is to design and implement repeatable and sustainable innovation processes to ensure innovation culture within OPERAS and foster innovative solutions for open scholarly communication in Social Sciences Humanities (SSH). To achieve this, the OPERAS Innovation Lab engages with the OPERAS Community, OPERAS Bodies and the Open Science Community as a whole, including Industry. The poster will present the current state of Lab’s implementation. The Lab offers two main services: the Observatory and the Accelerator. The Observatory performs innovation research and aims to produce knowledge on innovation in the SSH. The Accelerator facilitates innovation implementation in and around OPERAS through piloting solutions to the most pressing challenges in open scholarly communication in the SSH. The Lab’s operations are being communicated through its website (https://lab.operas-eu.org/), offering a wide range of materials discussing innovation and current activities of the Lab. The poster will highlight the role of assessing innovation within research assessment models in the SSH. Understanding and improving innovation assessment is one of the core tasks for the Lab and the team aims to engage the community to tackle this challenge collaboratively.